Training in Writing English Couplets Based on Structuralism for Students of SMAN 19 Surabaya - Wijaya, Kusuma; Pasopati, Rommel Utungga; Hariyono, Hariyono; Tobing, Victor Maruli Tua L.; Putri, Laura Ika Angelina Arfina; Simbolon, Sinta Uli (Gudang Jurnal Pengabdian Masyarakat, 2025)
This article explains the report in community service of training in writing English couplets for students of SMAN 19 Surabaya in 2024. Couplets are one of English literary works, especially poems, in which two lines of verse are joined in a rhyme. Writing couplets is important to dig understanding about both indications of structures in English poems alongside students’ creative imaginations. Structuralism is a perspective that underlines analysis of structures in English language, especially through English literary works. It is also known that structure in English language is meant to be universal rather than particular. Through an exploratory approach within qualitative research, this manuscript underscores structuralism as a way to identify aspects of literature regarding training of writing couplets. Couplet is a work that pays attention to pouring imaginations from the authors’ mind towards a structured sense of lyrical poem. Though the ideas come from various authors’ imaginations, this kind of literature and its writing process may still open to various possibilities in advance. In conclusion, the training of writing couplets is essential not only to give knowledge about patterns of poems in English literature, but also to get it in line with students’ everyday experience and imaginations.